Use of antidepressants and risk of repeat self‐harm in older adults 75+ with nonfatal self‐harm: A 1‐year prospective national study. Issue 2 (2nd November 2021) - Hedna, Khedidja; Montuori, Chiara; Forte, Alberto; Pompili, Maurizio; Waern, Margda
Abstract: Purpose: To assess exposure to antidepressants (AD) before and after nonfatal self‐harm (SH) in older adults and to examine 1‐year rates and risk factors for subsequent SH. Methods: Longitudinal national register‐based retrospective cohort study of Swedish residents aged 75+ ( N = 2775) with treatment at hospital or specialist outpatient clinic in connection with SH between January 1, 2006, and December 31, 2013. The cohort was followed for 1 year after the index episode. Exposure to AD was assessed at index and at subsequent SH. Cox regression analysis was used to assess factors associated with 1‐year repeat SH. Results: At the index episode, 51% were prevalent AD users; 23% started AD during the following year. Overall 12% of prevalent AD users, 8% of AD nonusers, and 6% of AD new users repeated SH or died by suicide. About two‐thirds of these subsequent behaviors occurred within 3 months after the index episode. Men had increased risk of subsequent SH (Hazard ratio [HR] 1.38, 95% CI: 1.09–1.74); older age (>85 years) was associated with a lower risk (HR 0.72, CI 95% 0.55–0.93). Users of AD did not have an increased risk of repeat SH. Conclusions: Half of older adults who self‐harmed were prevalent AD users and a further one fourth started an AD within 1 year after the index SH. Antidepressant use was not associated with increased risk of subsequent SH in this high‐risk cohort of older adults.